Interleukin 6 Present in Inflammatory Ascites from Advanced Epithelial Ovarian Cancer Patients Promotes Tumor Necrosis Factor Receptor 2-Expressing Regulatory T Cells - Kampan, Nirmala Chandralega; Madondo, Mutsa Tatenda; McNally, Orla M.; Stephens, Andrew N.; Quinn, Michael A.; Plebanski, Magdalena (Frontiers in Immunology, 2017)
Background: Epithelial ovarian cancer (EOC) remains a highly lethal gynaecological malignancy. Ascites, an accumulation of peritoneal fluid present in one third of patients at presentation, is linked to poor prognosis. High levels of regulatory T cells (Tregs) in ascites are correlated with tumour progression and reduced survival. Malignant ascites harbours high levels of Tregs expressing the tumour necrosis factor receptor 2 (TNFR2), as well as pro-inflammatory factors such as interleukin 6 (IL-6) and tumour necrosis factor (TNF). IL-6 is also associated with poor prognosis. Herein, we study the effect of IL-6 and TNF present in ascites on the modulation of TNFR2 expression on T cells, and specifically Tregs. Methods: Ascites and respective peripheral blood sera were collected from 18 patients with advanced EOC and soluble biomarkers including IL-6, sTNFR2, IL-10, TGF-b and TNF were quantified using multiplexed bead-based immunoassay. Peripheral blood mononuclear cells (PBMC) from healthy donors were incubated with cell-free ascites for 48 hours (or media as a negative control). In some experiments, IL-6 or TNF within the ascites were neutralised by using monoclonal antibodies. with human monoclonal antibodies. The phenotype of TNFR2+ Tregs and TNFR2- Tregs and T were characterised effectors were characterised post incubation in ascites. In some experiments, cell sorted Tregs were utilised instead of PBMC. Results: High levels of immunosuppressive (sTNFR2, IL-10 and TGF-b) and pro-inflammatory cytokines (IL-6 and TNF) were present in malignant ascites. TNFR2 expression on all T cell subsets was higher in post culture in ascites and highest on CD4+CD25hiFoxP3+ Tregs, resulting in an increased TNFR2+ Treg/ effector T cell ratio. Furthermore, TNFR2+ Tregs conditioned in ascites expressed higher levels of the functional immunosuppressive molecules PD-L1, CTLA-4 and GARP. Functionally, TNFR2+ Tregs frequency was inversely correlated with interferon-gamma (IFN-y) production by effector T cells, and was uniquely able to suppress TNFR2+ T effectors. Blockade of IL-6, but not TNF, within ascites decreased TNFR2+ Treg frequency. Results indicating malignant ascites promotes TNFR2 expression and increased suppressive Treg activity using PBMC were confirmed using purified Treg subsets. Conclusions: IL-6 present in malignant ovarian cancer ascites promotes TNFR2 expression and frequency of highly suppressive Tregs.